Endobronchial ultrasound-guided transbronchial needle aspiration of lesions in mediastinum - Eckardt, Jens (Pioneer Bioscience Publishing Company, 2010)
BACKGROUND: Lesions in mediastinum can represent malignancy and warrants further workup. Commonly a diagnosis is achieved by conventional bronchoscopy, transbronchial needle aspiration or CT guided fine needle aspiration, however a number of patients remain undiagnosed despite these common investigations METHODS: During a period of 36 months 601 patients underwent EBUS at our institution. Two hundred ninety three patients had an established diagnosis of lung cancer and were referred to us for mediastinal staging. The remaining patients had a radiologically suspicious intrathoracic lesion of which 107 had an undiagnosed lesion in mediastinum. All patients had been investigated by previous chest CT and bronchoscopy including brush cytology but remained undiagnosed. RESULTS: Of the 107 patients with undiagnosed lesions in the mediastinum 89 enlarged lymph nodes and 18 mediastinal tumours. Forty-eight of the 89 patients (54%) with enlarged mediastinal lymph nodes were diagnosed by EBUS of the remaining 41 patients 11 went on to more invasive methods. In patients with undiagnosed tumours in mediastinum we achieved a final diagnosis by EBUS in 14 of the 18 patients (78%) and 3 went on to more invasive methods. CONCLUSION: EBUS provides a final diagnosis in 78% of patients with tumour in mediastinum and in more than half of patients with enlarged lymph nodes despite previous workup.